The relevance of the environmental planning and management (EPM) process to local government and the responsibilities of the local government: the case of sustainable Ibadan project (sip), Nigeria (1998)
Nigerian cities which are supposed to be development centres are currently plagued with environmental problems of various types. There has, however, been the recognition that better city management practices will facilitate attempts at minimizing those environmental problems. Moreover, combined efforts of the federal. state and local governments, as well as those of the private sector will be needed in order to deal effectively with urban problems. Using the participant - observation research approach, the paper investigates the relevance of environmental planning and management process to local governments, and identifies some of the roles of local governments within the process. It, in particular, highlights the roles of planners in facilitating activities of local governments in implementation of the sustainable Ibadan Programme (SIP). It argues that the environmental problems facing Ibadan Metropolis can be effectively addressed in a sustainable manner by application of participatory and interactive environmental planning and management (EPM) process